Diagnostic Microbiology: Present Status and Future Prospect (Bangladesh Journal of Infectious Diseases, 2017)
Diagnostic Microbiology is the tool that makes it possible to identify the exact pathogens of infectious diseases and the most optimal therapy at the level of individual patients. Conventional methods require time to grow the microbes in vitro under specific conditions and not all microbes can easily be cultured. This is followed by biochemical methods for identification which further makes the process lengthy. Transport of the specimens under less than ideal conditions, prior use of antibiotics and small number of organisms are among the factors that render culture-based methods less reliable. Newer methods depend on amplification of nucleic acids followed by use of probes for identification. This mitigates the need for higher microbial load, presence of metabolically active viable organisms and shortens the time. These methods can be used to detect antibiotic resistance genes directly from the specimen and help direct targeted therapy with efficacy. Since these methods will not fulfill all the diagnostic needs, a second approach is being used to shorten the time to identification after the organism has already grown. Mass spectrometry and bioinformatics are the tools making this possible. This review gives a historical perspective on diagnostic microbiology, discusses the pitfalls of current methodology and provides an overview of newer and future methods.Bangladesh Journal of Infectious Disease 2015;2(2):42-47